Biofabricated silver nanoparticles as green catalyst in the degradation of different textile dyes. Issue 1 (March 2016) - Bogireddy, Naveen Kumar Reddy; Kiran Kumar, Hoskote Anand; Mandal, Badal Kumar
Graphical abstract: The synthesised stable spherical AgNPs using S. acuminata fruit extract showed excellent catalytic activity in the reduction of 4-NP and degradation of MB, MO, PR and DB24 in the presence of NaBH4 as reducing agent. Degradation of organic dyes PR and DB24 using AgNPs as catalyst is reported first time herein. Highlights: Synthesis of spherical AgNPs using S. acuminata fruit extract. Illustration of possible mechanism involved in the synthesis of stable AgNPs. Catalytic efficiency of synthesized AgNPs in reduction/degradation of different organic dyes. This is 1st report on degradation of PR and DB24 by catalytic biogenic AgNPs. Abstract: Biogenic silver nanoparticles (AgNPs) synthesized by Sterculia acuminata fruit extract was characterized by UV–vis spectroscopy, XRD, TEM, FTIR, PSA, and Zeta potential studies. Formation of AgNPs is initially confirmed by UV–vis spectroscopic studies with the characteristic band at 426 nm. TEM and XRD reports revealed that AgNPs are highly crystalline and spherical in shape with average particle size of ∼10 nm. PSA studies revealed that average particle size of AgNPs is 10.3 nm which is in close agreement with TEM reports. FTIR studies indicated the presence of different functional groups on the surface of the AgNPs indicating the stability of AgNPs by capping of biomolecules onto the surface which is further supported by zeta potential studies with the negative zeta potential value of −39.2 mV. Further catalytic efficiency synthesized AgNPs was evaluated for the reduction/degradation of various organic dyes such as 4-nitrophenol (4-NP), methylene blue (MB), methyl orange (MO), phenol red (PR) and direct blue 24 (DB24). It was found that degradation of MB and DB24 was faster than that of other dyes. This is the first report on degradation of organic dyes PR and DB24 using NaBH4 as reducing agent in the presence of catalytic amount of AgNPs.